The Metamorphic Nature of the Tau Protein: Dynamic Flexibility Comes at a Cost - Sabbagh, Jonathan J.; Dickey, Chad A. (Frontiers in Neuroscience, 2016)
Accumulation of the microtubule associated protein tau occurs in several neurodegenerative diseases including Alzheimer’s disease (AD). The tau protein is intrinsically disordered, giving it unique structural properties that can be dynamically altered by post-translational modifications such as phosphorylation and cleavage. Over the last decade, technological advances in nuclear magnetic resonance (NMR) spectroscopy and structural modeling have permitted more in-depth insights into the nature of tau. These studies have helped elucidate how metamorphism of tau makes it ideally suited for dynamic microtubule regulation, but how it also facilitates tau self-assembly, oligomerization, and neurotoxicity. This review will focus on how the distinct structure of tau governs its function, accumulation, and toxicity as well as how other cellular factors such as molecular chaperones control these processes.